Titanium alloy
By developing a titanium alloy that optimizes ingredients, the problem of anti -fatigue, oxidation and mechanical strength in the application of existing titanium alloy above 550 ° C is solved. High -performance titanium alloy.
Patent Information
- Application Number
- CN202380044683.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-06-01
AI Technical Summary
Existing titanium alloys are not competitive in applications above 550°C, especially in terms of resistance to resident fatigue, oxidation and mechanical strength, which limits the working temperature and service life of the aviation propulsion system.
A titanium alloy with optimized ingredients contains 4.0 % to 5.0 % aluminum, 3.50 % to 4.50 % tin, 1.0 % to 4.0 % 锆, 2.0 % to 5.25 % molybdenum, 1.0 % to 2.50 % 铌 , 0.10 % to 0.25 % of silicon and 0.10 % to 0.18 % oxygen, the content of alloys is accurately adjusted to improve the fatigue, antioxidant, and mechanical strength of the alloy.
The alloy exhibits excellent corrosion resistance, oxidation resistance and mechanical strength at an operating temperature of 650°C. In particular, it outperforms existing titanium alloys in terms of resistance to dwell fatigue, and has a density comparable to existing titanium alloys.
Smart Images

Figure BDA0005166982470000041 
Figure BDA0005166982470000051 
Figure BDA0005166982470000052
Abstract
Description
Technical Field
[0001] The present invention relates to the field of metal alloys, and more particularly to alloys for use in the field of aerospace industry. Prior art
[0002] Reducing polluting emissions is a major challenge facing the aviation industry. A method often proposed to reduce these emissions is to increase the efficiency of the propulsion systems used. However, the effectiveness of these systems is limited by their operating temperature, which itself is limited by the materials that make up the propulsion system.
[0003] Furthermore, the material constituting the propulsion system must have sufficient mechanical properties for the propulsion system, especially the aircraft turbine engine, in addition to having good temperature resistance, especially in terms of mechanical strength, oxidation resistance and fatigue resistance.
[0004] It is well known that titanium alloys are used to manufacture compressor disks, compressor blades, compressor wheels or turbine engine nozzles.
[0005] Over time, the chemical composition of titanium alloys used for disks, blades, impellers or turbine engine nozzles has changed significantly, with the aim of increasing in particular their mechanical strength at temperature and resistance to the environments in which these alloys are used. The complexity of the chemical composition of these alloys can lead to instabilities in their optimal microstructure, so the choice of added elements and their content is not trivial.
[0006] The main advantage of these materials is the combination of high mechanical strength and density half that of nickel-based superalloys, with reasonable resistance to oxidation and corrosion, all at temperatures below 550°C.
[0007] Therefore, titanium alloys are competitive with steel or nickel-based superalloys at temperatures below 550°C. However, the increase in turbine engine operating temperatures requires an increase in temperature resistance, especially for commercial titanium alloys.
[0008] More precisely, the titanium alloys most commonly used in the aerospace industry are so-called "quasi-alpha" alloys, which contain a large portion of dense hexagonal alpha phase and the latter generally has good temperature resistance. For example, the Ti-6AI-2Sn-4Zr-2Mo alloy is a representative of this family.
[0009] However, quasi-alpha titanium alloys are not competitive in applications above 550°C for a number of reasons.
[0010] First, these alloys are susceptible to what is known as “dwell fatigue.” This fatigue can be described as a near-creep fatigue observed from ambient temperature, involving a period of holding under stress for several minutes.
[0011] Currently, quasi-alpha alloys have their service life limited by their susceptibility to "residual" fatigue. More specifically, while residential fatigue is not observed at high temperatures, it can still occur during engine cool-down cycles. In addition to resistance to "residual" fatigue, the desire to increase the operating temperature of aerospace propulsion systems has necessitated an increase in the oxidation resistance and mechanical strength of the materials used.
[0012] More specifically, increasing the operating temperature promotes damage to titanium alloys by corrosion, especially oxidation. In addition, mechanical properties decrease with increasing temperature, and, at target temperatures above 550°C, known quasi-alpha alloys do not have the resistance required for future applications.
[0013] Therefore, in order to improve the efficiency of aviation propulsion systems, it is necessary to develop new titanium alloy compositions. Summary of the invention
[0014] The present invention aims to meet this need and for this purpose proposes an alloy with an optimized composition to provide residence fatigue resistance, corrosion resistance and mechanical strength compatible with use in aircraft turbine engines at operating temperatures up to 650°C.
[0015] To this end, the present invention relates to a titanium alloy comprising, by weight:
[0016] -4.0% to 5.0% aluminum;
[0017] -3.50% to 4.50% tin;
[0018] -1.0% to 4.0% zirconium,
[0019] - 2.0% to 5.25% molybdenum;
[0020] - 1.0% to 2.50% niobium;
[0021] - 0.10% to 0.25% silicon;
[0022] -0.10% to 0.18% oxygen;
[0023] The remainder consists of titanium and unavoidable impurities;
[0024] The equivalent aluminum weight content of the alloy is recorded as Aleq, which is less than or equal to 8.5%, and is calculated using the following formula: Aleq = [AI] + [Sn] / 3 + [Zr] / 6 + 10 * [O], where [Al], [Sn], [Zr] and [O] are the weight contents of aluminum, tin, zirconium and oxygen in the alloy respectively.
[0025] The alloy is used to manufacture turbine engine components such as disks, blades, impellers or exhaust nozzles.
[0026] Throughout this application, unless otherwise stated, the amounts of elements given are by weight.
[0027] The inventors have the advantage of having obtained the alloy composition described, the behavior of which has been observed to enable this problem to be addressed. In fact, the alloy of the invention has, among other characteristics:
[0028] - Contains a density comparable to that of existing titanium alloys;
[0029] - Corrosion and oxidation resistant, compatible with turbine engine environments up to at least 650°C and at least above the temperatures of current commercial alloys;
[0030] - Mechanical strength, especially resistance to fatigue, is greater than that of existing alloys;
[0031] - have sufficient microstructural stability within the expected service temperature range, in particular up to 650°C;
[0032] - Low sensitivity to the formation of detrimental phases (eg ω-phase) within the expected temperature range of use, in particular at least up to 650° C.
[0033] The inventors have particularly noted that iron, chromium and nickel reduce the creep resistance of the alloy. Therefore, for high temperature applications, it is preferred to avoid the presence of these elements, as is the case in the alloy according to the invention.
[0034] In addition, the inventors have found that a weight content of equivalent aluminum less than or equal to 8.5%, or even less than or equal to 8.0%, makes it possible to limit the fraction of phase α2 in the alloy. For alloys with a weight content of equivalent aluminum higher than those described, a large fraction of phase α2 may occur, which can lead to undesirable embrittlement of the alloy. In addition, for alloys with a larger weight content of equivalent aluminum, it has been observed that the transformation kinetics of the α phase are too high, resulting in an increased sensitivity of the alloy to retained fatigue, which is what the alloy of the present invention is intended to avoid.
[0035] The inventors have succeeded in determining, on the one hand, the importance of the weight content criterion of equivalent aluminum as an important criterion for the existence of the phenomenon and, on the other hand, have proposed optimizing this by precisely adjusting the content of other elements in order to meet the technical specifications of alloys used in aviation turbine engines with an operating temperature of at least 550°C.
[0036] In one embodiment, the weight content of equivalent aluminum may be between 6.5% and 8.5%, or even between 6.5% and 8.0%.
[0037] In one embodiment, the alloy of the present invention comprises an aluminum content by weight of 4.0% to 4.8%, or even 4.0% to 4.7%.
[0038] The inventors have noted that this additional limitation of the aluminum content makes it possible to avoid precipitation of too large a fraction of the phase α2, α2 alloy, which increases the mechanical strength of the alloy and in particular its ductility.
[0039] In one embodiment, the alloy of the present invention comprises a molybdenum content between 4.50% and 5.25% by weight.
[0040] Molybdenum stabilizes the alloy's beta phase, contributing to solid solution strengthening. The beta phase helps increase the alloy's ductility, thereby improving its formability.
[0041] In one embodiment, the alloy may have a silicon content of between 0.1% and 0.15% by weight.
[0042] In fact, silicon contributes to solid solution strengthening and the formation of silicides, especially silicides with M3Si and M5Si3 stoichiometry, where M represents another element, such as titanium, zirconium, molybdenum or niobium. These silicides contribute to the creep resistance of the alloy, but too high a silicon content will lead to excessive precipitation of silicides, which will impair the ductility of the alloy and may become a crack initiation point, leading to premature degradation of the alloy.
[0043] The proposed silicon range is the one that achieves the best value between these two effects.
[0044] In one embodiment, the zirconium content may be between 1.0% and 2.0% by weight.
[0045] Zirconium tends to improve the oxidation resistance of the alloy. However, excessive additions of zirconium will stabilize the α2 phase, and too much α2 phase will reduce the ductility of the alloy. The recommended value is to find the optimum between the two effects.
[0046] According to another of its aspects, the invention relates to a turbine engine component comprising the alloy just described.
[0047] In one embodiment, such a component may be a compressor blade, a compressor disk, a compressor wheel, a turbine engine casing, or a turbine engine nozzle.
[0048] According to another of its aspects, the invention relates to a turbine engine comprising one or more turbine engine components as just described. DETAILED DESCRIPTION
[0049] The invention will now be described by way of examples which, for illustrative purposes, illustrate certain embodiments of the invention. The examples given should not be construed as limiting the invention.
[0050] In order to characterize the properties of some specific alloys of the invention, the inventors chose to use the results of numerical simulations. More precisely, 11 alloys according to the invention and three comparative alloys were the subject of predictive measurements in order to determine their ability to produce the expected capacity of the alloys.
[0051] The compositions of the alloys in question are given in the following Table 1. The three comparative examples are pseudo-alpha titanium alloys commonly used in the aerospace field.
[0052] Comparative alloy 1 (Comparative 1), corresponds to the so-called Ti6242S alloy.
[0053] Comparative alloy 2 (Comparative 2), corresponds to the so-called Ti6246 alloy.
[0054] Comparative alloy 3 (Comparative 3), corresponds to the so-called IMI-834 alloy, available for example from TIMET under the commercial reference 834 was purchased commercially.
[0055] [Form 1]
[0056]
[0057]
[0058] In order to understand the following examples and the conclusions that can be drawn, it should be noted that all properties of the alloy must be evaluated rather than considering one property in isolation.
[0059] Thus, for example, if we only look at density, we would consider the Comparison 3 alloy to be the most promising, but this does not take into account that this alloy cannot be used at high temperatures because its α2 phase content and its fractional slope at the β transformation are too high and its retained fatigue resistance is too low, as shown by the readings in Tables 2 and 5.
[0060] The optimization and selection of a specific alloy is always the result of a compromise between different properties and it is very important to look at all the important parameters that will be presented below to understand the alloy of particular interest for the invention to solve the technical problem.
[0061] The following examples are intended to present a comparison between different embodiments according to the invention and to show that these embodiments generally have better properties than the comparative alloys, but none of them are suitable for use under conventional conditions of aircraft turbines with operating temperatures between 550°C and 650°C.
[0062] The inventors first determined the densities of different alloys.
[0063] The density is determined by the law of mixtures, with the density of each element weighted by its weight content, reducing the overall by 2.5%. Therefore, the density of the alloy, ρ, can be written according to the following formula, where Wi is the mass percentage of element i, ρ i is its density.
[0064] [Mathematics 1]
[0065]
[0066] For comparative examples Comparative 1 to Comparative 3, this formula gave an error of the order of 1%, which is considered acceptable.
[0067] The densities of the embodiments and comparative examples are shown in Table 2.
[0068] [Table 2]
[0069] Reference Numbers <![CDATA[ρ(g.cm -3 )]]> Ex1 4.64 Ex2 4.65 Ex3 4.65 Ex4 4.68 Ex5 4.60 Ex6 4.66 Ex7 4.64 Ex8 4.70 Ex9 4.69 Ex10 4.77 Ex11 4.82 Comparison 1 4.53 Comparison 2 4.75 Contrast 3 4.51
[0070] The densities of different alloys are comparable to those of those alloys, and often even lower.
[0071] The second element of the comparison of the alloys according to the invention with the alloys of the prior art is their parabolic oxidation constant at 650° C., denoted k p .
[0072] This constant quantifies the oxidation kinetics (mass gain) of the alloy. The higher its value, the faster the surface oxide forms, or equivalently, the faster the oxygen diffuses within the alloy. Therefore, for the target application, it is desirable to keep this parameter as low as possible.
[0073] Table 3 lists the parabolic oxidation constants of the embodiments and comparative examples. For the embodiments and comparative examples according to the present invention, the constant k p Obtained through the collection and use of regression models based on experimental data.
[0074] [Table 3]
[0075] Reference Numbers <![CDATA[kp at 650 °C (×10 13 g 2 / cm 4 / s)]]> Ex1 1.68 Ex2 1.68 Ex3 1.53 Ex4 1.68 Ex5 2.26 Ex6 1.34 Ex7 1.14 Ex8 1.60 Ex9 1.32 Ex10 1.49 Ex11 1.49 Comparison 1 3.56 Comparison 2 4.35 Contrast 3 1.52
[0076] Table 3 shows that the alloy of the present invention has better oxidation resistance than the comparative examples 1 and 2 at 650°C.
[0077] Furthermore, it should be noted that these values are at least comparable to the third comparative example, which is the comparative example that exhibited the best antioxidant properties.
[0078] The alloys according to the invention were further compared with the comparative examples with respect to mechanical properties at room temperature and elevated temperature.
[0079] For this purpose, the tensile strength values Rm divided by the alloy density are reported in Table 4. Table 4 also includes the elongation at break A% at 20°C.
[0080] [Table 4]
[0081]
[0082] The values reported in Table 4 were obtained through the collection and use of regression models based on experimental data.
[0083] For the desired application, it is preferred that the mechanical strength values as well as the elongation are as high as possible.
[0084] Table 4 shows that the alloys according to the invention have mechanical strengths at room temperature and at temperatures that are at least of the same order of magnitude as the alloys of the prior art.
[0085] Table 4 further illustrates that the alloys according to the invention are able to compromise properties that cannot be achieved by the alloys of the prior art. For example, even though none of them has a higher mechanical strength at 650°C than the alloy of Comparative 3, almost all of them have a higher elongation at break.
[0086] Finally, certain thermodynamic properties of the alloys of the invention were also evaluated by numerical simulations, which ensure their good temperature resistance.
[0087] The simulations were performed by thermodynamic equilibrium calculations using the CALPHAD method using the commercial thermodynamic database TCTI3 (Thermo-Cale Software AB, Sweden).
[0088] The various thermodynamic properties thus evaluated are listed in Table 5 below.
[0089] [Table 5]
[0090]
[0091] In Table 5 , the symbol “-” indicates that the obtained value is not significant and the numerical result can be taken as 0.
[0092] The β-transus temperature characterizes the stability domain of the β phase. The lower the β-transus temperature, the more stable the β domain.
[0093] The Δα column represents the absolute difference between the fraction of α at equilibrium at 700°C and the fraction of α phase at equilibrium at 650°C. This is an indication of the extent to which the alloy structure changes between these two temperatures, demonstrating the stability of the alloy at these temperatures close to the expected use temperature. The goal is to keep the change Δα low, and it can be noted that all alloys of the invention have lower Δα values than the comparative example Comparative 2.
[0094] Table 5 also includes a column indicating the content of the α2 phase at equilibrium at 650°C.
[0095] If it is desired that the content of α2 phase be zero, low levels are not prohibited since this phase has been observed to contribute to strengthening by precipitation.
[0096] Table 5 also includes the silicide content. The presence of silicides in the alloy ensures a certain strengthening by precipitation, which is desired and observed for all alloys according to the invention.
[0097] Finally, Table 5 describes the slope of the alpha fraction at the beta transformation. This value is an indicator of the beta phase transformation kinetics upon cooling. It has been observed that too large values (absolute value) are associated with alloys in which the alpha precipitates have a morphology that increases the alloy's susceptibility to retained fatigue.
[0098] Furthermore, the Comparative 1 and Comparative 3 alloys are known to be sensitive to this fatigue mode and have relatively high values (absolute values) of the α-slope at the β transition.
[0099] In contrast, it is known that the Comparative 2 alloy is less susceptible to dwell fatigue. Since the values for the alloy according to the invention are relatively close to the slope values for the Comparative 2 alloy and in any case are much lower (in absolute terms) than the values for the Comparative 1 or Comparative 3 alloys, the alloy according to the invention is expected to have good resistance to dwell fatigue.
[0100] From the examples just given, we can see in particular that the alloys of comparative examples 1 and 2 present very high parabolic oxidation constants compared to the other alloys considered, while comparative alloys 3 and 1 do not give satisfactory results and their susceptibility to fatigue still exists.
[0101] On the other hand, the alloys of the present invention allow for acceptable behavior with respect to each of the important variables mentioned above, in particular:
[0102] - their oxidation behavior is more acceptable than that of the prior art Comparative 1 and Comparative 2 alloys, as evidenced by the parabolic oxidation constant kp which is much lower than that of the Comparative 1 and Comparative 2 alloys;
[0103] - their mechanical properties, defined by the constant Rm / p, are substantially close to those of the alloys of the prior art, in particular the elongation at break is generally higher than that of the alloys of the comparative examples;
[0104] - Increased resistance to dwell fatigue compared to the prior art Comparative 3 (and Comparative 1) alloys, as evidenced by the slope value of the alpha fraction at the beta transition.
[0105] Thus, the alloys of the present invention are better candidates for use in higher temperature applications than prior art alloys because they offer a better compromise than prior art alloys, for which at least one property does not allow them to be used at higher temperatures.
[0106] Throughout the application, unless otherwise stated, all value ranges must be understood to include the range boundaries.
Claims
1. A titanium alloy comprising, by weight: -4.0% to 5.0% aluminum; -3.50% to 4.50% tin; -1.0% to 4.0% zirconium, - 2.0% to 5.25% molybdenum; - 1.0% to 2.50% niobium; - 0.10% to 0.25% silicon; -0.10% to 0.18% oxygen; The remainder consists of titanium and unavoidable impurities; The equivalent aluminum weight content of the alloy is recorded as Aleq, which is less than or equal to 8.5%, and is calculated using the following formula: Aleq = [AI] + [Sn] / 3 + [Zr] / 6 + 10 * [O], where [Al], [Sn], [Zr] and [O] are the weight contents of aluminum, tin, zirconium and oxygen in the alloy respectively.
2. The titanium alloy according to claim 1, wherein The weight content of equivalent aluminum is between 6.5% and 8.0%.
3. The titanium alloy according to claim 1 or 2, wherein: The aluminum content is between 4.0% and 4.8% by weight.
4. The titanium alloy according to any one of claims 1 to 3, wherein The weight content of molybdenum is 4.50% to 5.25%.
5. The titanium alloy according to any one of claims 1 to 4, wherein The weight content of silicon is 0.1% to 0.15%.
6. The titanium alloy according to any one of claims 1 to 5, wherein The zirconium weight content is 1.0% to 2.0%.
7. A turbine component comprising the alloy according to any one of claims 1 to 6.
8. The turbine engine component of claim 7, the component being selected from a compressor blade, a compressor disk, a compressor wheel, a turbine engine casing or a turbine engine nozzle.
9. A turbine engine comprising a component as claimed in claim 7 or 8.
Citation Information
Cited By
Component optimization design and preparation method of IMI834 titanium alloy bar with long load-holding fatigue life
CN121931382A